2010
DOI: 10.1007/s10404-010-0692-2
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic inverse phase ELISA via manipulation of magnetic beads

Abstract: We report a new technique for conducting immuno-diagnostics on a microfluidic platform. Rather than handling fluid reagents against a stationary solid phase, the platform manipulates analyte-coated magnetic beads through stationary plugs of fluid reagents to detect an antigenic analyte. These isolated but accessible plugs are preencapsulated in a microchannel by capillary force. We call this platform microfluidic inverse phase enzyme-linked immunosorbent assay (lIPELISA). lIPELISA has distinctive advantages in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…After the experiments for microchannels with hydrophilic surface, the channels were rendered hydrophobic by following procedure which was reported by Chen et al (2010). Solutions of 1H, 1H, 2H, 2H-perfluorooctyl-trichlorosilane (PFO-TCS; 4% v:v) filled the microchannels for 1 h in a closed chamber filled with dry nitrogen gas.…”
Section: Main Flow Channelmentioning
confidence: 99%
“…After the experiments for microchannels with hydrophilic surface, the channels were rendered hydrophobic by following procedure which was reported by Chen et al (2010). Solutions of 1H, 1H, 2H, 2H-perfluorooctyl-trichlorosilane (PFO-TCS; 4% v:v) filled the microchannels for 1 h in a closed chamber filled with dry nitrogen gas.…”
Section: Main Flow Channelmentioning
confidence: 99%
“…Shikida et al determined an average carry-over of 0.08 nL/mg using 150-600 mg of 32.7 mm MBs in a 10% KCl solution [5]. Chen et al reported 3.62 nL carry-over of water using 5 Â 10 5 MBs having a diameter of 3.12 mm amounting to approximately 0.37 nL/mg [6]. Sur et al used 40-180 mg of 450 nm MBs to estimate the carry-over of Tris buffer in their system amounting to 2.02 nL/mg.…”
Section: Introductionmentioning
confidence: 98%
“…This is done by transporting the target-MB cluster through an immiscible phase, such as oil [4][5][6], wax [4,7,8], or air [8], often using an external permanent magnet. Such systems have been demonstrated for a number of applications including enzyme linked immunosorbent assays [6,9,10], nucleic acid extraction [4,7,8,[11][12][13][14], protein extraction [8], and cell extraction [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive and comprehensive analysis of ferrofluidic manipulation on DMF devices has been previously reported therefore here we concentrate on aqueous droplets containing paramagnetic particles only [24,30,31]. Commercial "magnetic particles" for this purpose are based on (super)paramagnetic particles, where an iron oxide core is surrounded by a layer of silica, which can be functionalized as desired for a given application [32][33][34][35]. Many devices using magnetic actuation have been reported, and complex droplet movement has been demonstrated in three dimensions, including actuation of an inverted droplet [20].…”
Section: Introductionmentioning
confidence: 99%